(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The report presents analytical information about the state of play of the processes of the Fourth Industrial Revolution in different areas of the Bulgarian economy and industry. Based on a survey conducted in Bulgarian SMEs, the respondents' idea of the challenges and obstacles faced by company guides in its implementation in production, digital education, qualification and training in the course of the work is summarized. Data from a survey on key skills and competences needed to work in digitalization conditions have been released. Recommendations and sample applications have been formulated to ensure a successful symbiosis of Industry 4.0 with Industry 5.0.